Enhanced Lifetime and Photostability with Low‐Temperature Mesoporous ZnTiO3/Compact SnO2 Electrodes in Perovskite Solar Cells. (4th November 2019) - Guo, Fengwan; Sun, Xiangyu; Liu, Bing; Yang, Zijiang; Wei, Jing; Xu, Dongsheng
Abstract: Perovskite solar cells (PSCs) with power conversion efficiencies (PCEs) of 25 % mainly have SnO2 or TiO2 as electron‐transporting layers (ETLs). Now, zinc titanate (ZnTiO3, ZTO) is proposed as mesoporous ETLs owing to its weak photo‐effect, excellent carrier extraction, and transfer properties. Uniform mesoporous films were obtained by spinning coating the ZTO ink and annealed below 150 °C. Photovoltaic devices based on Cs0.05 FA0.81 MA0.14 PbI2.55 Br0.45 perovskite sandwiched between SnO2 ‐mesorporous ZTO electrode and Spiro‐OMeTAD layer achieved the PCE of 20.5 %. The PSCs retained more than 95 % of their original efficiency after 100 days lifetime test without being encapsulated. Additionally, the PSCs retained over 95 % of the initial performance when subjected at the maximum power point voltage for 120 h under AM 1.5 G illumination (100 mW cm −2 ), demonstrating superior working stability. The application of ZTO provides a better choice for ETLs of PSCs. Abstract : Gezinkte Solarzellen : Bei niedriger Temperatur verarbeitetes, UV‐inertes ZnTiO3 wurde als mesoporöse Schicht in SnO2 ‐basierte planare Perowskit‐Solarzellen eingeführt. ZnTiO3 modifiziert dabei die SnO2 /Perowskit‐Grenzfläche und verbessert die UV‐Stabilität sowie die Lebensdauer der Geräte deutlich. Die mesoporöse Niedrigtemperatur‐Struktur erweitert die Auswahlmöglichkeiten für Übertragungsschichten und Elektrodenmaterialien.